Effects of atrazine and endosulfan sulphate on the ecdysteroid system of Daphnia magna - Palma, Patrícia (2013)
The ecdysteroid system is used by crustaceans and other arthropods as the major endocrine signalling molecules, regulating processes such as molting and embryonic development. The aim of this study was to evaluate the ecdysteroid activity of two pesticides (atrazine and endosulfan sulphate), with distinct modes of action and which act in the juvenoid system of the crustacean Daphnia magna as weak juvenoid compounds. To assess the ecdysteroid activity, we first exposed maternal daphnids and embryos to nominal concentrations of the pesticides and determined the effect promoted by these pesticides on the molting frequency and on abnormalities in the embryos development. Furthermore, we evaluated if the toxic effects observed with the isolated pesticides were promoted or not by the disruption of the ecdysteroids system of the crustacean, by co-administrating of them with 20-hydroxyecdysone hormone. This hormone is the prime form of the invertebrate’s ecdysteroids system and it is responsible for the crustacean molting process. Both pesticides induced an increase of embryo abnormalities development. Endosulfan sulphate promoted a delay in the molting process. The effects induced by atrazine were not altered by co-exposure to 20-hydroxyecdysone. In contrast, the co-administration of 20-hydroxyecdysone allowed the reversion of the effects on both the molting process and embryonic development elicited by endosulfan sulphate. These results suggest that atrazine promotes its toxicity without interfering with the ecdysteroid activity of the crustacean. On the contrary, endosulfan sulphate is an anti-ecdysteroidal compound for D. magna.